The Nature of Social Studies Learning for Elementary School Students - Syafruddin, Syafruddin; Fadhilah, Fara; Rahmawati, Aulia; Komalasari, Anita; Rizqan, Nur (JUPE : Jurnal Pendidikan Mandala, 2024)
In essence, social studies learning is very important to be taught to students since they are in elementary school. The aim of social studies learning is to develop the potential of students to be sensitive to social problems that occur in society, to have a positive mental attitude towards correcting all inequality that occurs and to be skilled in dealing with every problem that occurs every day, whether it befalls them or others. This research uses the library research method. This research attempts to collect sources related to learning models that can be applied in the social studies learning process in elementary schools. The method used is the literature review method, which is a method that focuses on collecting literature related to the problem topic. After collecting literature related to the research focus, what the researcher does is select journals that can really be used, and group them according to the order of need, then analyze these sources and draw conclusions. Based on the results of studies that have been carried out, it can be seen that the essence of social science is a scientific discipline that studies humans, society and social interactions, which explains various phenomena or events in the social environment that have interactions within them. So that social science will integrate all scientific disciplines related to social science. Therefore, teachers need to develop teaching materials, so as to encourage students to learn actively.